Interoception and psychopathology: A developmental neuroscience perspective. (February 2017) - Murphy, Jennifer; Brewer, Rebecca; Catmur, Caroline; Bird, Geoffrey
Highlights: Reviews literature on the development of interoception. Atypical interoception may cause onset of psychopathology in adolescence. Atypical interoception may also cause risky behaviour in adolescence. Interoceptive changes may underlie socio-emotional changes in late adulthood. Abstract: Interoception refers to the perception of the physiological condition of the body, including hunger, temperature, and heart rate. There is a growing appreciation that interoception is integral to higher-order cognition. Indeed, existing research indicates an association between low interoceptive sensitivity and alexithymia (a difficulty identifying one's own emotion), underscoring the link between bodily and emotional awareness. Despite this appreciation, the developmental trajectory of interoception across the lifespan remains under-researched, with clear gaps in our understanding. This qualitative review and opinion paper provides a brief overview of interoception, discussing its relevance for developmental psychopathology, and highlighting measurement issues, before surveying the available work on interoception across four stages of development: infancy, childhood, adolescence and late adulthood. Where gaps in the literature addressing the development of interoception exist, we draw upon the association between alexithymia and interoception, using alexithymia as a possible marker of atypical interoception. Evidence indicates that interoceptive ability varies across development, and that this variance correlates with established age-related changes in cognition and with risk periods for the development of psychopathology. We suggest a theory within which atypical interoception underlies the onset of psychopathology and risky behaviour in adolescence, and the decreased socio-emotional competence observed in late adulthood.